2021
DOI: 10.1155/2021/5683433
|View full text |Cite|
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome Treated Using a Positive Pressure Ventilator Based on Artificial Intelligence Processor

Abstract: With the acceleration of people’s life rhythm, obstructive sleep apnea syndrome appears more and more frequently. This research mainly discusses the treatment of obstructive sleep apnea syndrome with a positive pressure ventilator based on artificial intelligence processor. The information storage function of the smart positive pressure ventilator is included in the local medical terminal, presented after logging in with the user authority. It is mainly composed of data collection, data processing, and medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Keeping the upper airway open is extremely important for patients with OSA to prevent upper airway collapse during sleep, as well as to help improve the patients' sleep quality. It is very often observed in patients who have varying severity of OSA-from moderate to severe (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping the upper airway open is extremely important for patients with OSA to prevent upper airway collapse during sleep, as well as to help improve the patients' sleep quality. It is very often observed in patients who have varying severity of OSA-from moderate to severe (5).…”
Section: Introductionmentioning
confidence: 99%
“…The data transmission mechanism allows the CPAP ventilator to be connected to the local medical terminal. CPAP data is collected, sent, and transmitted in real time for a fixed period (5).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%